The Reason Matters: Deep Wrist Injury Patterns Differ with Intentionality (Accident versus Suicide Attempt). Issue 5 (May 2019) - Kisch, Tobias; Matzkeit, Nico; Waldmann, Annika; Stang, Felix; Krämer, Robert; Schweiger, Ulrich; Mailänder, Peter; Westermair, Anna Lisa
Abstract : Background: Despite the clinical importance of suicidal deep wrist injuries (DWIs), we currently do not know whether their injury patterns differ from accidental injuries. Methods: This retrospective study included all patients admitted to the Clinic of Plastic Surgery for acute treatment of a DWI from 2008 to 2016, except for isolated injuries to the palmaris longus (PL) and amputations. Intentionality of the injury was determined using documentation of psychiatric evaluations; cases that could not be categorized regarding intentionality were excluded. Results: About 20% of DWIs stemmed from suicide attempts, which involved the nondominant hand in 94.5%. Suicidal DWIs were more likely to involve the median nerve, radial artery, PL, and flexor carpi radialis (FCR), especially on the nondominant hand, but were less likely to involve the ulnar artery and nerve on the dominant hand. The effect of the protective structures PL/flexor carpi ulnaris on the median nerve/ulnar artery could be confirmed for suicidal DWIs, but intactness of the FCR was associated with increased radial artery injuries. Longitudinal cut orientation in suicidal DWIs was associated with more radial artery injuries, but fewer injuries to tendons and nerves. Frequencies of various other injury constellations are tabulated to aid in clinical assessment. Conclusions: Suicidal and accidental DWIs differed in various aspects of injury pattern. Suicidal injuries were mostly localized to the nondominant radial side, and accidental injuries to the ulnar side. Also, the so-called protective structure FCR had the opposite effect in suicidal injuries. Thus, findings regarding injury patterns in accidental DWIs cannot be generalized to suicidal injuries.